Errors Made by Vocational School Students in Translating Analytical Exposition Text - Permatasari, Ayu; Yuliasri, Issy (Language Circle: Journal of Language and Literature, 2020)
The research aims to describe the kinds of translation errors made by vocational school students in translating analytical exposition text from English into Indonesian. The method used in the research was descriptive qualitative. The subject of the research was the eleventh graders of Fashion Program of SMK Al Asror Semarang. An analytical exposition text consisting of 5 paragraphs (source texts) and all of its’ translations in Indonesian (the target texts) were used in the research to find out the translation errors. Then the researchers classified them into 5 kinds of translation errors according to Vilar et al. (2006, p. 698). The results of the research revealed that there were 232 translation errors found in students’ translation. There were translation errors in the form of incorrect word (60.3%), punctuation (26.3%), missing word (6.0 %), word order (5.2%), and unknown words (2.2%). In conclusion, the three most prominent error categories made by the students were incorrect word, punctuation, and missing word errors.